Busca de compostos com ação citotóxica em Porcelia macrocarpa R. E. Fries (Annonaceae) - Ferreira, Loraine Elizabeth Martins [UNIFESP] (2015)
This work describes the evaluation of the in vitro cytotoxic activity and bioactivity guided fractionation of the extracts in hexane and CH2Cl2 of Porcelia macrocarpa seeds. In order to do this, extracts in hexane and CH2Cl2 were prepared and submitted to evaluation of the cytotoxic potential against B16F10Nex2 cell line (murine melanoma). As the CH2Cl2 extract displayed activity (cell viability 45±3% to 50 ?g/mL and 34±2% to 25 ?g/mL) it was fractionated on silica gel, resulting in a mixture of two acetylenic acetogenins which were purified using HPLC procedures. Analysis of 1H NMR spectra and 13C, as well as MS allowed the identification of 2-(eicos-11-yn-19-enyl)-3-hydroxy-4-methyl-?-lactone (I) and 2-(eicos-11-ynyl)-3-hydroxy-4-metil-? lactone (II). To establish relationships between the chemical structure / biological activity, the mixture of I and II was completely hydrogenated generating 2-eicosyl-3-hydroxy-4-methyl-?-lactone (III). The cytotoxicity of the compounds I and II was evaluated in vitro against various lineages of cancer cells, including murine (melanoma - B16F10Nex2) and human (breast - SKBR-3; ovary - Ovcar-3; cervix - Siha, colon and rectum - HCT ; Melanoma - A2058). The activity of the mixture of I + II is higher than the potential detected in the pure substances (IC50 values ranging from 21.0±0.3 to 28±1 ?g/mL). The compound I showed moderate potential against HCT and lines OVCAR-3 (IC50 of 83±3 and 81.0±0.1 ?g/mL), whereas compound II showed a reduced potential (IC50> 90 ?g/mL for all cells tested). These results suggest that the presence of a terminal double bond in the side chain could play a relavant role in the cytotoxic activity. Similarly, compound III was inactive (IC50> 100 ?g/mL for all tested cells) indicating that the presence of the triple bond in the side chain is also important to that potential.